Reduction in printing scrap using Failure Mode Effect Analysis (FMEA) approach - Jatin H Varma, Dr. Sachin Lal, (International Journal of Advanced Science and Technology, 2020)
The main purpose of this article is to identify the cause of printing scrap using FMEA approach and to suggest improvement measures. With FMEA proper models are developed to find critical failure, effect of failure, severity, critical causes and its occurrence in current process. Then with proper detection plan and by selecting standard RPN (Risk Priority Number) recommended actions are decided and implemented after consulting with experts. The improvement measures have been suggested based on part reduction, design changes and Analytic model approach. The action plan was developed in such way that the changes or developments in the process will be feasible and economical. The suggested improvement measures are implemented and check the reduction in printing scrap.